Notes from a liar and her dog - Choldenko, Gennifer (New York : Putnam's, 2001)
Eleven-year-old Ant, stuck in a family that she does not like, copes by pretending that her "real" parents are coming to rescue her, by loving her dog Pistachio, by volunteering at the zoo, and by bending the truth and telling lies.
Keywords: Family life; Honesty; Dogs; Zoos